Remarkable Tourist Products of Transcarpathia - Berghauer Sándor; Fodor Gyula; Бергхауер Олександр; Фодор Дюло (ЛДУФК ім. Івана Боберського, 2021)
Abstract. Despite all the late negative trends and processes that hinder its development, the tourism in Transcarpathia still has good chances to really become the key sector of the region’s economy. This is also true for the international tourism, as, prior to the coronavirus outbreak there was (and after the end of the pandemic hopefully will be again) a growing demand for untraditional, authentic destinations, with the global decrease of customer loyalty and the second, third holidays becoming more frequent. The rich historical past of Transcarpathia, its peripheral location within Ukraine, the ethnic and religious diversity as well as the development of the specific local cultural and natural values into new tourist attractions can provide an excellent basis for creating an adequate touristic image for the region. In addition, it should be noted that in present-day Ukraine the inner touristic demand, the ’culture’ of tourism is being formed now and it certainly affects the future of Transcarpathia.
Keywords: negative trends; Transcarpathia; health tourism; national demand